PENGARUH DESENTRALISASI PENDIDIKAN DASAR TERHADAP KUALITAS PENDIDIKAN DI KABUPATEN JEMBRANA PROVINSI BALI - Ujang Didi Supriyadi (Universitas Negeri Yogyakarta, 2009)
This study was aimed at finding out the results of the Education Decentralization Program implemented by the Government through the Decentralized Basic Education Project (DBEP). DBEP was a primary education decentralization project utilizing a loan fund from Asian Development Bank (ADB) and APBN/APBD aimed at increasing access and education quality for the poor society. The study took place at Jembrana Regency, in Bali Province, which had biggest count of poor population. Results showed that there was education quality improvement before and after the implementation of the education decentralization program. Based on mean difference statistical test, it could be concluded that there was significant difference in It was concluded that the primary education decentralization program had given a significant influence on the improvement of education quality in Jembrana Regency.